Carbon and sulfur isotopic signatures of ancient life and environment at the microbial scale: Neoarchean shales and carbonates. Issue 2 (24th October 2015) - Williford, K. H.; Ushikubo, T.; Lepot, K.; Kitajima, K.; Hallmann, C.; Spicuzza, M. J.; Kozdon, R.; Eigenbrode, J. L.; Summons, R. E.; Valley, J. W.
Abstract: An approach to coordinated, spatially resolved, in situ carbon isotope analysis of organic matter and carbonate minerals, and sulfur three‐ and four‐isotope analysis of pyrite with an unprecedented combination of spatial resolution, precision, and accuracy is described. Organic matter and pyrite from eleven rock samples of Neoarchean drill core express nearly the entire range of δ 13 C, δ 34 S, Δ 33 S, and Δ 36 S known from the geologic record, commonly in correlation with morphology, mineralogy, and elemental composition. A new analytical approach (including a set of organic calibration standards) to account for a strong correlation between H/C and instrumental bias in SIMS δ 13 C measurement of organic matter is identified. Small (2–3 μm) organic domains in carbonate matrices are analyzed with sub‐permil accuracy and precision. Separate 20‐ to 50‐μm domains of kerogen in a single 0.5 cm 3 sample of the 2.7 Ga Tumbiana Formation have δ 13 C = −52.3 ± 0.1‰ and −34.4 ± 0.1‰, likely preserving distinct signatures of methanotrophy and photoautotrophy. Pyrobitumen in the 2.6 Ga Jeerinah Formation and the 2.5 Ga Mount McRae Shale is systematically 13 C‐enriched relative to co‐occurring kerogen, and associations with uraniferous mineral grains suggest radiolytic alteration. A large range in sulfur isotopic compositions (including higher Δ 33 S and more extreme spatial gradients in Δ 33 S and Δ 36 S than any previously reported) are observed in correlation with morphology and associated mineralogy. Changing systematics of δ 34 S, Δ 33 S, and Δ 36 S, previously investigated at the millimeter to centimeter scale using bulk analysis, are shown to occur at the micrometer scale of individual pyrite grains. These results support the emerging view that the dampened signature of mass‐independent sulfur isotope fractionation (S‐MIF) associated with the Mesoarchean continued into the early Neoarchean, and that the connections between methane and sulfur metabolism affected the production and preservation of S‐MIF during the first half of the planet's history.